ANALISIS PERTUMBUHAN MINAT BELAJAR MIPA MAHASISWA PAPUA PADA JURUSAN PENDIDIKAN MIPA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS CENDERAWASIH TAHUN 2010 SAMPAI DENGAN 2014 - Antoh, Alfred A.; Siregar, Tiurlina (Jurnal Ilmu Pendidikan Indonesia, 2015)
This study aimed to: (1) To determine the amount and distribution of student interest Papuans to Mathematics, Physics, Chemistry and Biology in the Department of Mathematics and Science Education, Guidance and Counseling Uncen. (2) To see the level of the proportion and distribution of the number of indigenous Papuan students in the Department of Mathematics and Science Education, Guidance and Counseling Uncen courses. Existing data were then analyzed using descriptive statistics through the following steps: (a) is described, (b) presented (c) described verbally, and (d) inferred. The results obtained from this empirically is (1) It is a low number of indigenous Papuan students enrolled as a student at the Faculty of Mathematics and Natural Sciences Teaching and Education UNCEN or ranged between 10-15% of the total average number of them in Education Program Mathematics, Chemistry, Biology and Physics. (2) Students Papuans have a tendency to move the program to the social sciences as a result of the decline in the grade point average of students who continue to decline at the beginning of the semester one and two. Low ability students beginning their to move to the Science Program in Environmental social sciences FKIP or out to other faculty at the Cenderawasih University environment. Keywords : Papua, Interests, Mathematics and Science